Risk of cervical and vaginal dysplasia after surgery for vulvar intraepithelial neoplasia or cancer: a 6 year follow-up study - Buchanan, Tommy R. (Gynecol Oncol, 2019)
OBJECTIVES: To estimate the frequency of abnormal surveillance cytology leading to high-grade dysplasia after surgical management for high-grade vulvar intraepithelial neoplasia (VIN) and vulvar cancer and to determine whether prior hysterectomy reduces this risk. METHODS: Women who underwent surgery for high-grade VIN or vulvar cancer between 2006 and 2014 were identified retrospectively. Patients who underwent prior hysterectomy for any indication were included. Univariate and multivariate logistic regression analyses were used to identify clinical correlates of abnormal cytology after surgical treatment for VIN and vulvar cancer. RESULTS: During a median follow-up for 72 months, 302 women underwent surveillance with cytologic screening after vulvar surgery including 99 (33%) women with prior hysterectomy. 75 (25%) women had abnormal cytology results. Of those, 47 (63%) were low-grade and 28 (37%) were high-grade, including 2 (3%) cases of invasive cancer. The rates of high-grade vaginal intraepithelial neoplasia (VAIN), cervical intraepithelial neoplasia (CIN), or cancer were not significantly different despite prior hysterectomy (9% VAIN 2+, 7% CIN 2+). Multivariate analysis showed that correlates of high-grade cytology following treatment for VIN or vulvar cancer included non-white race [odds radio (OR) 3.6, 95% confidence interval (CI) 1.7–7.8], prior abnormal cytology (OR 3.5, 95% CI 1.6–7.6), and immunodeficiency (OR 3.4, 95% CI 1.3–8.8). Prior hysterectomy did not significantly decrease risk of high-grade cytology (OR 0.87, 95% CI 0.5–1.6). CONCLUSIONS: Women treated surgically for VIN/vulvar cancer have an 8% risk of at least high-grade dysplasia from surveillance screening and prior hysterectomy does not mitigate the risk. Extrapolating from current guidelines, we recommend surveillance cytology screening at least 6–12 months after treatment.